Assessment of genetic diversity within and among sage (Salvia) species using SRAP markers. Issue 3 (1st December 2015) - Aghaei, Zahra; Talebi, Majid; Rahimmalek, Mehdi
Abstract : Salvia (sage) is the most important and largest genus of the Lamiaceae family. High similarities among species in this genus lead to difficulty in its systematic identification. Despite its economic importance, limited molecular studies have been conducted to evaluate the genetic diversity among and within Salvia species. In this study, SRAP (sequence-related amplified polymorphism) markers, which targeted ORFs (open reading frames) as functional regions in the genome, were used to detect the genetic diversity of five Salvia species ( S. virgata Jacq., S. nemorosa L., S. officinalis L., S. cereal L. and S. sclarea L.). Fourteen primer combinations (PCs) were amplified by 265 fragments on 54 genotypes, in which 255 (96%) were polymorphic. The average polymorphism information content (PIC) value was 0.308 over all PCs. The genetic distance among species ranged from 0.126 (between S. virgata Jacq. and S. nemorosa L.) to 0.568 (between S. nemorosa L. and S. sclarea L.). Based on Jaccard's similarity coefficient and UPGMA algorithm, cluster analysis separated different species ( r = 0.920). The results showed high genetic differentiation ( F st = 0.337) and negligible gene flow ( N m = 0.750) among species. Owing to the high genetic variation among and within Salvia species, it serves as a rich source of germplasm with potential for use in breeding programmes.